Mechanical Characterisation of Carbon-Silica Reinforced Composites for Turbine Application - Sekunowo, Olatunde; Durowaye, Stephen; Ogunsina, Oluwabamibo (Journal of the Institute of Engineering, 2020)
Materials selection and development for application in advanced systems is becoming highly complex involving the need for lower cost alternatives without compromising service performance. This paper investigated selected critical mechanical properties of ceramic matrix composites synthesized from coconut shell carbon (CSC) reinforced with silica particles (SP). Coconut shells (CCS) and silica sand (SS) were pulverized separately in a plate mill and a ball mill respectively to obtain a particle size of 250 μm. The CCS powders were calcined at 5000 C in an oven to obtain coconut shell ash (CSA) which was carbonized in a furnace from 5000 C-10000 C under argon gas controlled environment. The materials were mechanically blended while the SP additions varied from 10-40 wt. % and compacted using hydraulic press. The compacted mixture was sintered at 5000 C-12000 C, held for 2 hrs and the composites characterised for mechanical properties while the microstructural integrity was analysed using scanning electron microscope/energy dispersive x-ray spectroscopy (SEM/EDS). Microstructure showed that after sintering, coconut shell carbon developed strong cohesion with the silica particles which gave rise to effective load transfer. The mechanical properties that ensued demonstrated on the average 52.8 % comparability with conventional power plant structural materials in terms of hardness, compressive strength and impact energy.